ANALISIS PENGENDALIAN KUALITAS MEMBRAN DALAM PERVAPORASI ETANOL-AIR DENGAN MENGGUNAKAN METODE STATISTICAL QUALITY CONTROL - Miftahul Djana; Rizka Mayasari (JISI: Jurnal Integrasi Sistem Industri, 2017)
Pervaporation is an alternative separation process using membrane which allows separations of organic mixtures and dehydrates organic solvents with low energy consumption. The purpose of this experiment is to analyze the influence of operating parameters such as feed temperature, times, variation of feed ethanol water mixtures, variation of membranes on pervaporation performance shown by the flux and selectivity by using ceramic membranes with variation of diatomaceous earth and clay as separation. Pervaporation process performance is determined from permeate selectivity and flux. Increase of permeate selectivity and flux means also increasing performace of pervaporation. However, increasing product flux may contribute on decreasing selectivity. The research consists of membrane preparation, pervaporation process, and optimization. Feed of this research are ethanol-water mixture with temperature varying between 40-60oC and downstream pressure 0.5 mbar. Ceramic membrane is used and modification with 30,60,90% of diatomaceous earth. From the results, the membranes have successfully improved the flux of this research..The results showed that the operating conditions of 0,5mbar pressure of permeate, the variation in temperatures of 40ºC, 50ºC and º, th variation of membranes and times produces the flux increases and selectivity decreases.In these conditions the maximum temperature, 60ºC gives the flux of 0,1945 l/m2.hr and the selectivity of 1,7198. In these conditions produce fuel grade ethanol with purity levels reached 98% from 95% ethanol feed.The test results indicated the mean value of t = 31.400> t table = 2.00 and sig. =0,000 <α = 0.05, thus the average (mean) of 1.806 issignificant. Thus the hypothesis that the level of damage membrane of the product significantly affect the processproduction is not proven.